The interactions between natural enemies and their role in controlling Bactericera cockerelli in potatoes - MacDonald, F.H.; Walker, G.P. (New Zealand Plant Protection, 2012)
The impacts of naturally occurring predators for control of Bactericera cockerelli (tomatopotato psyllid; TPP) have been assessed in potatoes at Pukekohe for 3 years Results indicate that the most commonly found predator species are Micromus tasmaniae (brown lacewing) and Melanostoma fasciatum (small hoverfly) with populations of small hoverfly eggs and larvae reaching up to almost 200 per plant in unsprayed plants over January and February Continuing with intensive studies on TPP these naturally occurring predators appear to be important biological control agents In laboratory choice and no choice assays results indicate these two predator species eat all life stages of TPP even in the presence of aphids The intraguild interactions between predator species are now being investigated to ascertain from a suite of predators on potatoes which are likely to be the best allies in developing an Integrated Pest Management (IPM) programme for potatoes Laboratory studies indicate that larvae of small hoverfly and larval and adult life stages of Coccinella undecimpunctata (11spotted ladybird) may be displacing brown lacewings